Effects of a grouping intervention using the Felder-Silverman learning style model on problem-based learning among nursing students: A randomized controlled trial. - Wu, Yifan; Song, Dongpo; Dong, Yueyang; Zhong, Qiqing; Gao, Shizheng; Sun, Juanjuan; Fang, Shuyan; Zhi, Shengze; Wang, Rui; Sun, Jiao (Nurse Education Today, 2025)
Problem-Based Learning (PBL) education can improve nursing students' thinking skills and overall quality of life, but its effectiveness depends largely on the level of student engagement within the group. Finding an intervention to increase nursing students' classroom engagement is critical to improving learning outcomes. To explore the impact of a grouping intervention using the Felder-Silverman Learning Style Model (FSLSM) on PBL in nursing education, including classroom engagement, critical thinking, self-directed learning skills, and academic performance. A single-center, single-blind, double-arm, parallel randomized controlled trial. One university school of nursing. The sample consisted of 56 fourth-year undergraduate nursing students. Students were randomly assigned to experimental group (n = 28) and control group (n = 28). The experimental group received PBL education based on FSLSM grouping and control group received traditional PBL education. Data collection was done using Demographic questionnaire, Index of Learning Style scale, Classroom Engagement Questionnaire for Students, Critical Thinking Disposition Inventory-Chinese Version, and Self-Directed Learning Skill scale. The data were analyzed using descriptive statistics, paired t -test, independent t -test, and chi-square test. The FSLSM-based grouping significantly enhanced classroom engagement and critical thinking in the experimental group compared to the control group. While both groups improved in self-directed learning skills, the experimental group showed greater gains in learning motivation and information quality. However, academic performance did not differ significantly between groups. Integrating the FSLSM with PBL can potentially optimize educational outcomes in nursing, emphasizing the importance of individual learning styles in group-based learning environments. The trial was registered at the Chinese Clinical Trials Registry (ChiCTR2300069565). • FSLSM-based grouping allows students with different learning styles to form a group with complementary skills and promotes mutual learning. • FSLSM-based grouping can improve the level of classroom engagement in PBL education, thus enhancing the effectiveness of PBL. • FSLSM-based grouping promotes critical thinking and self-directed learning skills in nursing students, facilitating nursing talent building.